IKLIM KOMUNIKASI ORGANISASI PEGAWAI DI KEPROTOKOLAN DAN KEUANGAN KANTOR GUBERNUR PROVINSI SUMATERA BARAT - Rina Wiyanti; Yummil Hasan; Usman Usman (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This research uses a qualitative method, with a descriptive approach. This study tried to obtain data in the form of written or oral words from several informants. The pattern of communication that occurs in the general bureau of the Governor's Office of West Suimatera Province is the Linear communication pattern, because in this pattern communicators and communicants face to face or the occurrence of feedback. Communication between superiors and subordinates in the public bureau by way of face to face. But not only face to face, but also done through non-electronic media such as letters, bulletin boards and so on or electronic media such as e-mail, whatshap, telephone and so on. The results showed that in the general bureau of the governor's office in the province of West Sumatra, the communication pattern was effective. In the public bureau, if there is a conflict between fellow subordinates, then the boss's way of resolving the problem is by asking for food.